Alcohol, hepatitis C screening and hepatic fibrosis in drug users - Di Nino F; Chaffraix F; Schaeffer M; Doffoel M (Open Journal of Hepatology - Peertechz Publications, 2019)
Background: In drug users, viral hepatitis C, alcohol abuse, and drug use are three interconnected public health challenges. Methods: This study assessed the impact of alcohol on hepatitis C screening and hepatic fibrosis in this patient population. In total, 934 substance users were included and divided into three groups: Group A, alcohol use disorder only (n = 511); Group ISDU, intravenous and snorting drug users (n = 142); Group ISDAU, intravenous and snorting drug users with alcohol use disorder (n = 281). A FibroScan was performed first, after which participants were proposed to undergo screening for HCV. Results: The HCV screening rate was significantly lower in Group A (62%) than in the ISDAU or ISDU groups (81% and 85% respectively) (p<0.001). The rate of HCV seropositivity was lower in Group A (4.4%), whereas it was significantly higher in the ISDAU group than ISDU group (42.3% vs 30.0%, p = 0.02). The rates of significant fibrosis and severe fibrosis were higher in Group A (34% and 21%) and the ISDAU group (29% and 18%) than in ISDU (15% and 7%) (p<0.001). While entering, in addition to the group, age, gender, smoking status (cannabis and tobacco), drug consummation, HCV seropositivity, and BMI as co-variables in a multivariate model, only age correlated with fibrosis (p<0.001). Considering age, there was no difference in impact among the different substances on the fibrosis score. Conclusion: Alcohol consumption impacts the health status of drug users. It is thus appropriate to early identify alcohol consumption in drug users and consider alcohol as a risk factor for severe fibrosis and HCV transmission. Alcohol consumption warrants the strengthening of HCV screening and hepatic fibrosis assessment.